Biodegradable amino acid-based poly(ester amine) with tunable immunomodulating properties and their in vitro and in vivo wound healing studies in diabetic rats' wounds. (15th January 2019) - He, Mingyu; Sun, Luyao; Fu, Xiaoling; McDonough, Sean P.; Chu, Chih-Chang
Graphical abstract: Abstract: The objective of this study is to design a new family of biodegradable synthetic polymeric biomaterials for providing a tunable inhibition of macrophage's nitric oxide synthase (NOS) pathway. l -Arginine (Arg) is the common substrate for NOS and arginase. Both two metabolic pathways participate in the wound healing process. An impaired wound healing, such as diabetic or other chronic wounds is usually associated with an overproduction of NO by macrophages via the NOS pathway. In this study, a new family of l -nitroarginine (NOArg) based polyester amide (NOArg-PEA) and NOArg-Arg PEA copolymers (co-PEA) were designed and synthesized with different composition ratios. The NOArg-PEA and NOArg-Arg co-PEAs are biodegradable (more than 50% degradation in vitro in 4 days at 37 °C), biocompatible and did not activate the resting macrophage immune response per se. When classically activated or alternatively activated macrophages (CAM/AAM) were incubated with NOArg-PEA and NOArg-Arg co-PEAs, the treatments decreased the NO production of CAM, increased the arginase activity in both CAM and AAM, increased TGF-β1 production of CAM to various degrees and had no significant effect on TNF-α production. Diabetic rat models were used to evaluate the efficacy of NOArg-PEA and NOArg-Arg co-PEAs on wound healing. Diabetic rats treated with 2-NOArg-4 PEA, 2-NOArg-4-Arg-4 20/80, and 2-NOArg-4-Arg-4 50/50 biomaterials achieved 40%–80% faster-wound healing when compared with the control on day 7. The data from the histological and immunohistochemical analysis showed that the 2-NOArg-4-Arg-4 20/80 and 2-NOArg-4-Arg-4 50/50 treatments led to more AAM phenotypes (CD206) and arginase I production in wound tissue than the control during the first 7 days, i.e., suggesting pro-healing wound microenvironment with improved re-epithelialization of wound healing. A similar trend was retained until day 14. The 2-NOArg-4-Arg-4 20/80 and 2-NOArg-4-Arg-4 50/50 treatments also increased the collagen deposition and angiogenesis in the healing wound between day 7 and day 14. Both in vitro and in vivo data of this study showed that this new family of NOArg-Arg co-PEA biomaterials have the potential as viable alternatives for treating impaired wound healing, such as diabetic or other types of chronic wounds. Statement of Significance: Diabetic or other chronic wounds is usually associated with an overproduction of NO and pro-inflammatory signals by macrophages. Arginine supplement or NOS inhibitors administration failed to achieve an expected improved wound healing because of the dynamic complexity of arginine catabolism, the difficulty in transition from pro-inflammatory to pro-healing, and the short-term efficacy. We designed and synthesized a new family of water-soluble and degradable nitroarginine-arginine polyester amides to rebalance NOS/arginase metabolism pathways of macrophages. They showed tunable immunomodulating properties in vitro. The in vivo studies were performed to evaluate their efficacy in accelerating the healing. These new biomaterials have the potential as viable alternatives for treating impaired wound healing. The general audience of Acta Biomaterialia should be interested in these findings.